2007
DOI: 10.1016/j.physb.2006.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Size effects and depolarization field influence on the phase diagrams of cylindrical ferroelectric nanoparticles

Abstract: Ferroelectric nanoparticles of different shape and their nanocomposites are actively studied in modern physics. Because of their applications in many fields of nanotechnology, the size effects and the possible disappearance of ferroelectricity at a critical particle volume attract a growing scientific interest. In this paper we study the size effects of the cylindrical nanoparticle phase diagrams allowing for effective surface tension and depolarization field influence. The Euler-Lagrange equations were solved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
1
35
0
3
Order By: Relevance
“…In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces. Here the homogeneous polarization distribution is affected by complex factors, 1,8,[28][29][30][31][32][33][34][35] such as surface discontinuity of the ferroelectric layer, 8,27,31,32 and Schottky barriers at interface, etc. 10,14,27,29 Theories and experiments on FNCs taking various forms such as nanodisks ͑ND͒, nanorods ͑NR͒, nanowires ͑NW͒, and nanotubes ͑NT͒ have indicated that their phase-transition or near-phase-transition properties are very sensitive to the applied stress.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 2 more Smart Citations
“…In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces. Here the homogeneous polarization distribution is affected by complex factors, 1,8,[28][29][30][31][32][33][34][35] such as surface discontinuity of the ferroelectric layer, 8,27,31,32 and Schottky barriers at interface, etc. 10,14,27,29 Theories and experiments on FNCs taking various forms such as nanodisks ͑ND͒, nanorods ͑NR͒, nanowires ͑NW͒, and nanotubes ͑NT͒ have indicated that their phase-transition or near-phase-transition properties are very sensitive to the applied stress.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…10,14,27,29 Theories and experiments on FNCs taking various forms such as nanodisks ͑ND͒, nanorods ͑NR͒, nanowires ͑NW͒, and nanotubes ͑NT͒ have indicated that their phase-transition or near-phase-transition properties are very sensitive to the applied stress. [33][34][35][36][37][38][39][40][41][42] In these investigations, stresses produced by surface tension and external mechanical loads have been found to significantly affect the Curie temperature, polarization, susceptibility and other related properties near the ferro/ paraelectric phase transition, resulting in remnant polarization and coercive fields that may exceed the bulk values. Indeed, under an uniaxial load of suitable magnitude and frequency, an appropriately dimensioned ferroelectric NW may produce a sizeable ac voltage, sufficient as a nanopower source for energy harvesting, or as an effective nanomechanical sensor.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of progress has been made toward understanding nanoscale effects on ferromagnetic properties, however the formalism for describing finite size and shape effects on ferroelectric properties is less developed. There are various reports in the literature describing complete suppression of ferroelectric behavior at nanoscale sizes as well as unusual phase transitions in nanodisks [3][4][5]. An in-depth understanding can be obtained by observing simultaneously the polarization, shape, and size of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…These observations have stimulated an exponential growth on research aiming to understand the effect of scaling on the ferroelectric properties. Recently, some theoretical studies predicted an enhancement of ferroelectricity in anisotropic "cylindrical" shaped particles 7 and a new kind of ferroelectric order for ferroelectric nanoparticles with one-dimension (1D) structure as nanotubes, nanowires, nanorods, nanobelts, nanofibres. 8 Morphology control and fabrication of ferroelectric nanoparticles with different shapes are then important.…”
Section: Introductionmentioning
confidence: 99%